Comparative Performance of Volatility Models for Oil Price - Salisu, Afees A.; Fasanya, Ismail O. (International Journal of Energy Economics and Policy, 2012)
In this paper, we compare the performance of volatility models for oil price using daily returns of WTI. The innovations of this paper are in two folds: (i) we analyse the oil price across three sub samples namely period before, during and after the global financial crisis, (ii) we also analyse the comparative performance of both symmetric and asymmetric volatility models for the oil price. We find that oil price was most volatile during the global financial crises compared to other sub samples. Based on the appropriate model selection criteria, the asymmetric GARCH models appear superior to the symmetric ones in dealing with oil price volatility. This finding indicates evidence of leverage effects in the oil market and ignoring these effects in oil price modelling will lead to serious biases and misleading results. Keywords: Crude oil price; Volatility modelling; Global financial crisis JEL Classifications: C22; G01; Q40